A Probabilistic Model for Fire Temperature Rise in High-Rise Residential Buildings under the Action of Uncertain Factors - Jiyao Yin; Tianyao Tang; Guowei Zhang; Lin Zhou; Peng Deng (Fire, 2023)
Due to the randomness of interior combustibles, wall thermal inertia, and opening factor, the fire temperature rise in high-rise residential buildings is uncertain. This study investigated 38 urban high-rise residential buildings, created the probability density functions of fire load density, opening factor, and wall thermal inertia, and constructed random fire scenarios for urban high-rise residential buildings. On this basis, relying on the Latin Hypercube Sampling method, this study further explored the probabilistic model for fire temperature rise in urban high-rise residential buildings under the action of uncertain factors, generated the possible temperature rise curves of fires in urban high-rise residential buildings and their probability distribution, and established the most representative temperature rise curve.